Effectiveness of a calcium sodium phosphosilicate containing prophylaxis paste in reducing dentine hypersensitivity immediately and 4 weeks after a single application: a double‐blind randomized controlled trial. (17th February 2013) - Neuhaus, Klaus W.; Milleman, Jeffery L.; Milleman, Kimberly R.; Mongiello, Kimberly A.; Simonton, Thomas C.; Clark, Courtney E.; Proskin, Howard M.; Seemann, Rainer
Abstract Aims The aim of this single‐site, randomized, controlled, double‐blind, 3‐arm parallel study was to determine the effectiveness of a prophylaxis paste containing 15% calcium sodium phosphosilicate (CSPS; NovaMin®) with and without fluoride in reducing dentine hypersensitivity immediately after a single application and 28 days following dental scaling and root planing. Materials & Methods Overall, 151 subjects were enrolled in this study. All subjects received a scaling and root planing procedure followed by a final prophylaxis step using one of three different prophylaxis pastes: Test‐A (15% NovaMin® and NaF), Test‐B (15% NovaMin®) and a control. Dentine hypersensitivity was assessed by tactile stimulus (Yeaple Probe®) and by air blast (Schiff scale) at baseline, immediately after and 28 days after a prophylaxis procedure. One hundred and forty‐nine subjects completed the study. Results Subjects having received the test prophylaxis pastes showed statistically lower (anova, p < 0.05) dentine hypersensitivity compared with the control group immediately after the prophylaxis procedure (Yeaple Probe®: Test‐A = 20.9 ± 12.6, Test‐B = 22.7 ± 12.9, Control=11.2 ± 3.1; Schiff score: Test‐A = 1.1 ± 0.6, Test‐B = 1.1 ± 0.6, Control = 2.0 ± 0.7) and after 28 days (Yeaple probe: Test‐A = 21.5 ± 11.9, Test‐B = 20.6 ± 11.3, Control = 11.8 ± 6.0; Schiff score: Test‐A = 1.0 ± 0.6, Test‐B = 1.0 ± 0.6, Control = 2.0 ± 0.7). Conclusions In conclusion, the single application of both fluoridated and non‐fluoridated prophylaxis pastes containing 15% CSPS (NovaMin®) provided a significant reduction of dentine hypersensitivity up to at least 28 days.